QUALITY OF LIFE, QUALITY OF LIFE IN THE WORKPLACE AND THE NR-17: BEYOND WHAT IS LEGAL (Fiep Bulletin - online, 2015)
The present study will argue the normative aspects, contained in the Norm Regulations 17, the NR-17, which must assure the health of the worker, having as a backdrop the quality of life and quality of life in the workplace. One is about an exploratory study that had as research procedure a literature revision. It was verified that the current law, guideline in the organization of the labor environment, is insufficient to guarantee the quality of life of the worker. It was inferred that the humanization of the work is a necessity that will not be guaranteed only with a legal apparatus, more is necessary.
Keywords: Quality of Life; Quality of Life in the Workplace; Norm Regulations 17 (NR-17).